Runoff and runoff chemistry from the catchment areas Risfallet and Gusseltjärn January 2012 to July 2013 - Lundin, Lars; Nilsson, Torbjörn (Swedish University of Agricultural Sciences, 2019)
Daily discharge (l/s) and runoff (mm/day) values, and monthly values on runoff chemistry from two small catchment areas; Risfallet (0.45 km2) and Gusseltjärn (0.87 km2) located in the southeast part of central Sweden. The Risfallet area was fertilized with nitrogen (Skog-CAN) in July 2012 and the Gusseltjärn area was used as a reference area.

Dagliga strömnings- (l/s) och avrinningsvärden (mm/dag) och månatliga värden på avrinningskemi från två små avrinningsområden; Risfallet (0,45 km2) och Gusseltjärn (0,87 km2) som ligger i den sydöstra delen av centrala Sverige. Risfallet-området gödslas med kväve (Skog-CAN) i juli 2012 och Gusseltjärnområdet användes som kontrollområde.
Avrinning och avrinningskemi från avrinningsområdena Risfallet och Gusseltjärn januari 2012 till juli 2013
Keywords: NITROGEN COMPOUNDS; NUTRIENTS; WATER QUALITY/WATER CHEMISTRY; CONDUCTIVITY; pH; ALKALINITY; SURFACE WATER; DISCHARGE/FLOW; Agricultural and aquaculture facilities; Jordbruks- och vattenbruksanläggningar; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Biological Sciences; Biologi